A multi-objective evolutionary algorithm based on adaptive clustering for energy-aware batch scheduling problem - Qian, Si-yuan; Jia, Zhao-hong; Li, Kai (Future generation computer systems, 2020)
For batch scheduling problems, more and more attentions have been paid to reducing energy consumption. In this paper, a complex batch scheduling problem on parallel batch processing machines considering time-of-use electricity price is investigated to minimize makespan and total electricity cost, simultaneously. Due to NP-hardness of the studied problem, a multi-objective evolutionary algorithm based on adaptive clustering is proposed, where an improved adaptive clustering method is incorporated to mine the distribution structure of solutions, which can be used to guide the search. Moreover, a new recombination strategy based on both distribution characteristics and mating probability is designed to select individuals for mating. In addition, to better balance exploration and exploitation, the mating probability is adaptively adjusted according to historical information. The experimental results demonstrate the competitiveness of the proposed algorithm in terms of solution quality. •Distribution characteristics of solutions are extracted by adaptive clustering.•A new recombination restriction strategy in reproduction is designed .•An adaptive adjustment of mating probability is proposed.